(untitled) (Ar-Raudhah: Journal of Islamic Religious Education, 2025)
This study aims to analyze the curriculum development in non-formal education at Madrasah Diniyah Bahjatul Ulum Al Bahrullah, Tigasan Wetan Village, Probolinggo. This madrasah focuses on teaching Islamic education with the goal of providing applicable religious knowledge to children in the surrounding area. Despite facing challenges such as limited facilities, funding, and the number of students, the madrasah has successfully implemented a practical-based curriculum. This study identifies the strengths and weaknesses of the curriculum applied, as well as key challenges, such as the madrasah’s status not being officially registered and the limitations in resources. Additionally, opportunities such as the development of a technology-based curriculum and collaboration with educational institutions or donors are explored. The recommendations provided include the implementation of educational technology, fundraising, and the development of a more relevant curriculum. This study offers insights for madrasah administrators and stakeholders to enhance the quality of non-formal education in rural areas.